To be The First or to be The Best: New Product Quality and Timing in R&D Competition - Shirish D. Chikte; Sudhakar D. Deshmukh (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
Better quality products usually command bigger market shares and higher profits for the firm. However, developing better products also requires higher R&D expenditures and longer development times, during which a competing firm may develop and introduce its product first and capture a share of the market. IN equilibrium, competing firms must balance these two effects in determining their product quality and timing decisions. We model this R&D competition between two dissimilar firms as a stochastic stopping game and investigate the nature of its equilibrium. In equilibrium, each firm sets a reservation level of the product quality it aims to develop. The technologically stronger firm is shown to set a higher quality target and command a higher market share and profit. Competition to be the first inducs each firm to introduce lower quality products earlier than it would as a monopolist. However, the net social benefit is shown to be higher with competition than that with just the weaker firm as a monopolist, although the stronger firm as a monopolist is shown to yield an even more desireable outcome, which in fact turns out to be socially optimal. Finally, if the firms are identical, this socially optimal outcome is also attainable with competition, and in fact it is attained at pace faster than that witth the strong monopolist or centrally controlled R&D.
Keywords: 330